A qualitative study to investigate pharmacovigilance systems in Dubai hospitals - Sawsan Shanableh; Muaed Jamal Alomar; Hadzliana Zainail (PLoS ONE, 2025)
Background Ensuring the safety of medications is a significant public health priority, with developed countries implementing robust pharmacovigilance programs. Despite this, healthcare providers continue to underreport adverse drug reactions (ADRs). This study aims to explore the existing pharmacovigilance system and procedure followed for ADR reporting in selected Dubai hospitals. It also identifies the obstacles that may negatively influence ADR reporting. Methods This study was conducted using a qualitative methodology involving in-depth interviews. Convenience sampling was used to select and interview chief hospital pharmacists in Dubai using a semi-structured interview guide. Every interview was audio recorded, verbatim transcribed, and then subjected to a thematic content analysis. The data were analyzed manually by the reading and re-reading of the interviews, and an inductive and flexible approach was undertaken by the research team. Results A total of ten individuals, three chief pharmacists and seven pharmacy managers were interviewed. Seven themes emerged from the interviews’ thematic content analysis, including: (1) Existence of a pharmacovigilance center or unit, (2) Experience with medication safety & ADR concept, (3) Current ADR reporting process in the hospital setting, (4) Barriers to adverse drug reaction reporting, (5) Policy change needs, (6) The factors that could enhance ADR reporting, and (7) Future pharmacovigilance research needs in the UAE. Eight hospitals have ADR reporting systems in their hospital policies while two hospitals don’t have any pharmacovigilance system. Of the eight hospitals, seven have their own software for ADR reporting and one used paper form. Based on the participants feedback, six have full experience with ADR reporting process, while others have partial or don’t have any idea about reporting process. ADR reporting is hindered by a number of factors, such as inadequate awareness and training for pharmacovigilance and ADR reporting process, a communication gap between hospitals and regulatory bodies, time constraints due to numerous responsibilities, and fear of punishment. Conclusion The study found that although hospital pharmacists have a good understanding of medication safety and ADR reporting, they do not actually apply this knowledge into practice. Ongoing training and education on the ADR reporting process have the potential to improve attitudes toward ADR reporting and actively engage individuals in ensuring medication safety within hospital settings. The participation of key stakeholders from the Ministry of Health, academia, the pharmaceutical companies, and healthcare professionals is essential to support the safe and effective use of medications.